Governing Cyberviolence in China: Limitations of the Cyberviolence Information Governance Provisions - Zhao, Yuxuan (International Journal of Social Sciences and Public Administration, 2026)
Cyberviolence, as a side effect of increasing internet penetration, is now prevalent worldwide. To combat the risks and acts of cyberviolence, in 2024, the Chinese government implemented its special regulation over ‘cyberviolence information’. These new ‘Provisions’ not only constitute an important part of the Chinese cybersecurity framework but also advance it from a reactive model to a proactive model, from governing behaviours to governing information. More notably, it greatly expands platforms’ role in cyber governance and empowers them to carry out content moderation and manage user accounts. However, ‘cyberviolence information’ is too broad and inaccurate of a legal concept to be used for censoring online speech and over-criminalizing legitimate communication. The strategy of ‘privatization of regulation’ and the empowered ‘digital Leviathan’ also pose severe threats to future Chinese development of the rule of law and democracy.